2014
DOI: 10.1521/psyc.2014.77.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Interpersonal Hostile-Dominance in Psychiatric Inpatients

Abstract: HD reflects a characteristic tendency toward interpersonal, affective, and behavioral problems marked by hostility and dominance, combined with a tendency toward frequent aggressive script rehearsal and more severe psychiatric symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Many symptoms relate to social perception, anger and hostility (e.g., paranoia will increase hostile attributions) (Podubinski, Lee, Hollander & Daffern, 2014) and aggression and violence more directly (Douglas, Guy, & Hart, 2009). Future research should ensure assessment of psychiatric symptoms alongside assessment of other risk factors so that change in the dynamic risks can be interpreted in line with change in psychiatric symptoms.…”
mentioning
confidence: 99%
“…Many symptoms relate to social perception, anger and hostility (e.g., paranoia will increase hostile attributions) (Podubinski, Lee, Hollander & Daffern, 2014) and aggression and violence more directly (Douglas, Guy, & Hart, 2009). Future research should ensure assessment of psychiatric symptoms alongside assessment of other risk factors so that change in the dynamic risks can be interpreted in line with change in psychiatric symptoms.…”
mentioning
confidence: 99%
“…For the purpose of the current research, PANSS items were grouped into five subscales (Negative, Positive, Disorganized, Excited, and Emotional Distress), in accordance with Kelley, White, Compton, and Harvey (). The Emotional Distress subscale was not used as analysis conducted in the full sample of 200 participants in the cross‐sectional component of this study found that this subscale was not associated with HD (Podubinski et al, ).…”
Section: Methodsmentioning
confidence: 94%
“…Participants were eligible for this study if admitted to one of the two inpatient units of the Alfred Hospital Department of Psychiatry (Alfred Psychiatry), Melbourne, Australia, between the 12th January 2012 and 10th October 2012. During the study period, 746 patients were admitted to the Alfred Psychiatry inpatient units and 200 (27%) chose to participate in the cross‐sectional component of this study (reported in Podubinski, Lee, Hollander, & Daffern, ). Forty‐one participants (21% of patients who completed the cross‐sectional component) were available to take part in a 6‐month follow‐up study, with 126 not able to be followed‐up due to not having current contact information or not answering phone calls from the research team, nine not consenting to follow‐up contact when initially interviewed, three being too unwell to participate, and 21 refusing consent for follow‐up.…”
Section: Methodsmentioning
confidence: 99%
“…Participants are required to respond according to a 7-point Likert scale ranging from "Never" to "Several times a day". The SIV frequency item has been used to assess the frequency of aggressive script rehearsal in clinical and forensic populations and it has consistently been found to be associated with aggressive behavior (Daff et al, 2014;Gilbert & Daffern, 2010;Podubinski et al, 2014).…”
Section: Frequency Of Aggressive Script Rehearsalmentioning
confidence: 99%